Among Musculoskeletal Surgeons, Job Dissatisfaction Is Associated With Burnout. Issue 8 (August 2016) - van Wulfften Palthe, Olivier D. R.; Neuhaus, Valentin; Janssen, Stein J.; Guitton, Thierry G.; Ring, David
Abstract: Background: Burnout is common in professions such as medicine in which employees have frequent and often stressful interpersonal interactions where empathy and emotional control are important. Burnout can lead to decreased effectiveness at work, negative health outcomes, and less job satisfaction. A relationship between burnout and job satisfaction is established for several types of physicians but is less studied among surgeons who treat musculoskeletal conditions. Questions/purposes: We asked: (1) For surgeons treating musculoskeletal conditions, what risk factors are associated with worse job dissatisfaction? (2) What risk factors are associated with burnout symptoms? Methods: Two hundred ten (52% of all active members of the Science of Variation Group [SOVG]) surgeons who treat musculoskeletal conditions (94% orthopaedic surgeons and 6% trauma surgeons; in Europe, general trauma surgeons do most of the fracture surgery) completed the Global Job Satisfaction instrument, Shirom‐Malamed Burnout Measure, and provided practice and surgeon characteristics. Most surgeons were male (193 surgeons, 92%) and most were academically employed (186 surgeons, 89%). Factors independently associated with job satisfaction and burnout were identified with multivariable analysis. Results: Greater symptoms of burnout (β, −7.13; standard error [SE], 0.75; 95% CI, −8.60 to −5.66; p < 0.001; adjusted R 2, 0.33) was the only factor independently associated with lower job satisfaction. Having children (β, −0.45; SE, 0.0.21; 95% CI, −0.85 to −0.043; p = 0.030; adjusted R 2, 0.046) was the only factor independently associated with fewer symptoms of burnout. Conclusions: Among an active research group of largely academic surgeons treating musculoskeletal conditions, most are satisfied with their job. Efforts to limit burnout and job satisfaction by optimizing engagement in and deriving meaning from the work are effective in other settings and merit attention among surgeons. Level of Evidence: Level II, prognostic study.